Developing speaking skills module for engineering students - Noor Raha, Mohd Radzuan; Fatimah, Ali; Kassim, Hafizoah; Hashim, Haslinda; Najah, Osman; Ramle, Abid (2006)
Expectations on a graduate looking for employment are many. Educational institutions are constantly working towards producing graduates to meet and exceed the requirements of the job market, and hence, increasing the employability of graduates. The reasons for this being: effects of globalization, increased number of communicative events in the engineering profession and meeting the needs of the industry that will employ the graduates. Thus, taking into consideration these challenges, this research aims to find out the most common communicative events that engineers are engaged in and finally to prepare KUKTEM students for these events by developing an effective module of Speaking Skills for engineering students. 66 engineers from different organizations responded to the questionnaires, while 29 and 25 subjects were engaged as subjects in the study for experimental and control group respectively. Verbal and written responses and feedback from subjects are highly considered in refining the developed module to be more effective.